Houseplants for beginners : a simple guide for new plant parents for making houseplants thrive - Steinkopf, Lisa Eldred, 1966- (New Shoe Press, 2023)
Choose the right houseplants for your space and then help them thrive with Houseplants for Beginners at your side. Having happy, healthy plants can make a space feel happy and healthy too. They add color, texture, and beauty--and can also improve air quality. For new plant parents eager for these benefits, this affordable, adapted edition of Houseplants by Lisa Eldred Steinkopf offers easy-to-understand information and advice. Each chapter deals with a key element of houseplant care, including light, water, soil, potting, and containers. The book also offers details on how to pick the right plants for your specific living situation. Go beyond just keeping your plants alive to understanding how to make them thrive...This book is organized to take you from starter plants to caring for more adventurous choices like tropical, climbing, and flowering species. This is the resource you can depend on to take you from your very first plant to seasoned plant parent.